Evaluation of the Efficacy of Tofacitinib, a JAK Inhibitor, in Alleviating Sepsis-Induced Multiple Organ Dysfunction Syndrome - Singh, Vaishnavi; Joshi, Kavita; Chatterjee, Samit; Qureshi, Sameer; Siddh, Snigdha; Nunia, Vandana (Drug Research, 2024)
Sepsis, a life-threatening condition triggered by an uncontrolled response to infection, results in a systemic inflammatory response syndrome (SIRS) and the failure of multiple organs leading to multiple organ dysfunction (MODS). In the present study, we investigated the therapeutic potential of tofacitinib (TOFA), an FDA-approved inhibitor of JAK1 and JAK3 against sepsis, using a mouse model induced by cecal ligation puncture (CLP). Swiss albino mice were employed to replicate the CLP-induced sepsis model and were randomly divided into four groups: control, CLP, 150 mg/kg TOFA, and 300 mg/kg TOFA. Six hours after the last TOFA dose, we collected blood and tissue samples from the liver, lungs, kidneys, and spleen for histological analysis. Blood samples were used to assess granulocyte and lymphocyte percentages. Throughout the experiment, we monitored body weight and short-term survival. Our comparative histological analysis revealed that 150 mg/kg TOFA had a protective effect against multiple organ damage. Conversely, the study highlighted the harmful effects of 300 mg/kg TOFA, primarily due to liver and renal toxicity within this group. In summary, our findings demonstrate that tofacitinib at an optimal dose of 150 mg/kg showed promise as a potential therapeutic intervention for sepsis-induced multiple organ failure. However, caution is warranted when considering higher dosages.
Keywords: sepsis; molecular docking; tofacitinib; multiple organ dysfunction; cecal ligation puncture; histopathology